Molecular Perspective on Pancreatic Cancers with a Focus on Genetics, Genomics, and Diagnostics - Baral, İnanç; Atessahin, Dilek Arslan; Öztürk, Mustafa Murat; Kaya, Şeyda; Daştan, Sevgi Durna (My University, 2026)
The pancreas stands out as a complicated organ vital for maintaining physiological balance with its exocrine and endocrine roles. It is aimed to present the genetic underpinnings of working basis of pancreas and its diseases with related biochemical pathways, especially with a focus on pancreatic cancers (PC). This article collects all current research and filters data about pancreatic biology and the molecular genetic backgrounds, and genomics pathways related pancreatic diseases. The pancreas has the highest number of different genetic disorders, which are always multifactorial. The pancreatic adenocarcinoma are particularly significant due to their rapid metastatic potential, extreme lethality, and surprising mortality rates. Various studies have revealed the different causes of the development of pancreatic cancers. And it is seen that it may be both a somatic and hereditary type of cancer. Some very important research has emphasised a substantial but insufficient network of gene-phenotype relationships for several mutations and susceptibility loci. This article collects the detailed perspective about existing literature to underline the molecular view of pancreatic cancers based on genetic, genomic and diagnostic principles.  This article focus on isolated aspects such as genomics or diagnostics, this review provides an integrated perspective combining molecular genetics, genomic instability, and emerging diagnostic approaches. By synthesizing findings across multiple disciplines, this study highlights the importance of a systems-level understanding of pancreatic cancer and proposes a framework for future research directions.
Keywords: Onkoloji; Gastroenteroloji ve Hepatoloji; Genetik ve Kalıtım